DOCUMENTARY ANALYSIS OF THE NEW CODE OF MEDICAL ETHICS IN THE LIGHT OF HUMAN RIGHTS - Passos Soares, Francisco José (2024)
Introduction: professional codes of ethics should be updated periodically to respond to criticisms and demands arising from social, technological and scientific changes, especially in the field of human rights; Objectives: to verify the updating of the new Brazilian Code of Medical Ethics in the field of bioethics and human rights; Methods: document analysis of a document in the public domain, with previous definition of categories of analysis and registration units, with reference to the Unesco Universal Declaration of Bioethics and Human Rights. Results: the analysis showed the following most prevalent principles: dignity, autonomy, respect for human vulnerability and personal integrity, benefit and harmful effects, solidarity, privacy and confidentiality, non-discrimination and non-stigmatization; Not very well covered: people without the capacity for consent, social responsibility, protection of the environment and future generations; Absent: sharing of research benefits, equality, justice and equity, respect for cultural diversity and pluralism; Final considerations: the Brazilian Code of Medical Ethics values the maintenance of prudential autonomy in the relationship with patients and health professionals. The inclusion of broader social concerns, in a fragmentary and insufficient way, does not yet ensure the broad defense of public health, and the rights of people in vulnerability, who have historically been in a position of disparity. The application of the method in a specific context, of the pandemic, was useful for the understanding of the deontological and principlist limits applied to public health. A future revision is suggested based on Unesco's Universal Declaration of Bioethics and Human Rights and the deliberative method for interprofessional decision-making.